The Metabolic and Neurochemical Etiopathology of Passive Exposition to Alcohol Consumers - Nery, Lamothe; Mara, Lamothe; Daniel, Lamothe; Ernesto, Villanueva; Pilar, Bueno; Alejandro, Alonso-Altamirano; Adriana, Clemente-Herrera; Estuardo, Hernández; Francisco, Guillermo Castillo-Vázquez; Andrės, Gerardo Roche (Journal of Public Health International, 2021)
A narrative review considers metabolic and neurochemical pathways implicated in passive exposure to alcohol consumers, discussing health effects and research needs.
Keywords: Passive Health Victims